The Impact of VAT Policy on Tax Compliance and Its Implications on Tax Revenue in the Real Estate Sector - Alwava, Rachmana; Nanik Kustiningsih (Universitas Ciputra Surabaya, 2024)
Abstract - The government faces the challenging task of collecting revenues to reinvigorate the economy and reduce the budget deficit caused by the pandemic. Various fiscal policies have been established to stimulate the economy. This study aims to determine the impact of changes in tariffs, the provision of incentives, and VAT supervision on tax compliance and its implications for state revenue. This research is worth repeating due to inconsistencies in previous research findings and discrepancies between conclusions and facts, as well as to evaluate the policies that have been implemented. This research employs a quantitative approach with saturated sampling method on time series data of real estate sector VAT revenue at the XYZ Tax Office. The testing technique involves classical assumption tests and path analysis using the SPSS program. The research findings indicate that tariff changes have a significant influence on tax compliance, while incentives and VAT supervision do not have a significant impact. Tariff changes and supervision significantly affect VAT revenues, whereas the provision of incentives does not have a significant impact. Tax compliance mediates the effect of tariff changes on VAT revenues, but it does not mediate the relationship between the provision of incentives and supervision on VAT revenues.